PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KARTU SIMPATI TELKOMSEL PADA MAHASISWA FAKULTAS EKONOMI PROGRAM S1 UNIVERSITAS SUMATERA UTARA - Yulia Kristina Simbolon; Marhayanie Marhayanie (Jurnal Media Informasi Manajemen, 2013)
Abstract The objective of this research is knowing the influence of marketing mix strategy towards purchasing decisions Simpati Telkomsel Card at faculty of Economics undergraduate program students University of North Sumatera. The kind of this research is explanatory research. Analysis method to test the hypotezis by using multiple linier regression, simultaneous test and partial test. SPSS 16.0 for windows was used to calculate and analyze the data of research. The data that used consist of primer and secondary data. This research used 96 respondents which determined by using accidental Sampling. The result of this research by multiple regression test shows that based on simultaneous test marketing mix strategy consist of Product, Price, Promotion, and Place have positive and significant influence towards purchasing decisions Simpati Telkomsel Card at faculty of Economics undergraduate program students University of North Sumatera. And based on partial test showed that the price variable has the most dominant influence towards purchasing decisions Simpati Telkomsel Card at faculty of Economics undergraduate program students University of North Sumatera. And calculating the coefficient of determination (R2) obtained a value of 0.338 means that the determinant of the independent variables of product, price, promotion, and location of the dependent variable is able to explain the purchase decision of 33.8% and the remaining 66.2% is explained by other variables not examined in this study. Keywords: Marketing Mix Strategy consist of Product, Price, Promotion, Place and Purchasing Decision.